Sorption and Availability of Potassium in Selected Soils from Western Kenya - Kituyi , Lusweti; Olukusi , Alwala Joseck (African Journal of Education,Science and Technology (AJEST), 2015)
Sorption is one of the most important processes in the soil which affects the fate, mobility and availability of nutrients. This process also takes into account intensity, quantity and capacity factors which are important for predicting the amount of nutrients required for maximum plant growth. A field study on sorption and availability of potassium (K) in soils sampled from maize and sugar cane growing sites of Sioya, Tabuti and Watoya in Bungoma County was conducted. The purpose of the study was to determine the effect of pH, organic matter and K+ ion levels on adsorption capacity of the soils. Sampled soils from each site at 0-20 cm depths were air dried, ground and sieved through 2 mm sieve. Jenwey pH meter measured soil pH; organic matter was determined by standard method while K+ ions were determined using flame photometer. Adsorption isotherms were evaluated by equilibrating soils with different K+ ionic levels in deionized water. The results show that the mean pH levels in the three areas were 6.25, 5.90 and 5.91 while organic matter was 5.1597, 5.4553 and 15.0367, respectively. Although the amount of K+ adsorbed was similar in the three sites and was found to increase with organic matter and pH, there was a significant difference (p ≤ 0.05) with these two parameters. The results fitted to both the Langmuir and Freundlich isotherms showing these two models successfully describe the K+ adsorption process with R2 values > 0.95. However, the data fitted better to the Langmuir isotherm, implying sorption process is a surface, homogeneous and monolayer in these soils. Organic matter and liming should be applied to the soils in the study areas in order to increase K+ adsorption.